Core guidelines for the discharge home of the child on long term assisted ventilation in the United Kingdom. Issue 9 (1st September 1998) - Jardine, Elspeth; Wallis, Colin
Abstract : Paediatric home ventilation is a feasible option and can be successful in a wide range of conditions and ages. Advances in ventilator technology and an ethos of optimism for home care has increased the possibilities for discharging chronically ventilated children from intensive care units and acute medical beds. With careful planning the process can succeed, but difficulties often thwart the responsible team, especially when attempting discharge for the first time. These core guidelines aim to assist a smooth, swift and successful transfer. They were developed by a working party of interested professionals spanning a wide range of health care disciplines and represent a synthesis of views accumulated from the experiences of individual teams throughout the UK. Three case scenarios provide further illustrative detail and guidance.